AIR SOVEREIGNTY AND NO-FLY ZONES - Agus Pramono (Fakultas Hukum, Universitas Diponegoro, 2016)
Sovereignty of a state in essence is an embedded, basic element of a state as a supreme power. However, the sovereignty of a state can only be applied within its own borders, where outside of its own territory the sovereignty of another country takes over. This research was carried out based on the approach of current legal regulations and review of literature. The study showed that airspace sovereignty is, in principle, embedded to a state of which ownership is exclusive in nature. No-fly zones are airspace in which a sovereign state determines to be restricted for flight traffic based on the existing international and national regulations. Keywords: State sovereignty, No-fly zone, International law